Changing Concepts for a Changing World. (2nd April 2018) - Sparks, Colin
Abstract : This article argues that some of the core concepts that are used in the study of media and communication are obsolete. This obsolescence is the product of three major factors: the continued dominance of the field by the Global North; the impact of digital technologies upon the existing media; and the continued view that everywhere in the world is evolving towards capitalist democracy. In each of these cases, experiences specific to particular times and places have been universalized and used to guide research in radically different conditions. Revisiting these inadequate universalizations and generating more inclusive substitutes is an urgent intellectual task.